Kvinde-Evangeliet: Om Grundtvigs mandebilleder og kvindesyner - Jonas, Uffe (Grundtvig-studier, 2007)
Kvinde-Evangeliet: Om Grundtvigs mandebilleder og kvindesyner[The Women ’s Gospel: On Grundtvig ’s images of men and women]By Uffe Jonas Grundtvig’s ideals of maleness and femaleness stand in complex relationship. He has generally been perceived as a classic patriarch, pater familias, father of both nation and church, of which he was a chosen prophet. This prophetic-patriarchal pillar makes up what might reasonably be called the masculine column of his work. Yet at the same time his domestic roles engaged him with the feminine side of life and supplied him with a fund of personal and intimate experience.From this he drew much of his life-philosophy, which is sensitive, sensible and erotic through and through. Not only was he a great and faithful lover of women, but his images of manliness are permeated by feminine ideals such as dialogue, wisdom, poetry, compassion, tenderness, human equality. With a strongly masculine pathos, he tends to favour feminine values and virtues as heralding the future in a modem world - seen not only in a social and political perspective but also, and to a larger extent, in the philosophical or spiritual perspectives from which his surprisingly positive views on womanhood originate.He was a European thinker and a universalist whose primitive-Christian viewpoint gave him a well developed sense of both the strengths and the delusions of modernity and, not least, of a new more liberal perception of womanhood - to which he himself was a significant contributor. He operated within a clearly established hierarchy of values, in which the love of his people was only one among the components of an ever increasing tonality of personal human and divine connections.Patriotism and the movement for national revival were certainly at the core of his political activities, but stood neither first nor highest in his spiritual scale of values, where concepts of the humane and the Christian were more highly cherished. Indeed, his national, popular and political concerns, which gave rise to the Grundtvigian movement, are only meaningful if seen in the superior philosophical, humane, and spiritual perspectives within which he himself conceived them.National revivalism was in itself an international phenomenon, and Grundtvig was a European philosopher and Christian universalist both before and after he became the Danish national standard bearer.Essential aspects of his thinking were overlooked, misperceived or even actively repressed in that national-popular foreshortening of perspectives entailed in the establishment of Grundtvigianism as a historical and political force. Lost in this process were Grundtvig’s highly personal and advanced philosophical, theological and even cosmological views on womankind, which instead led a kind of shadow existence at a semi-articulated level within the “late patriarchal system” of early Grundtvigianism - never completely out of the picture, but rather worked on the anecdotal level, on solemn and celebratory occasions, where they have served as an important historical and poetical inspiration through generations whilst at the same time not causing too much immediate trouble at the more intricate levels of social and sexual checks and balances.Thus in Grundtvig’s thinking all human progress and enlightenment, in fact the entire development of humanity itself, stands under the living, breeding and life-bringing sign of a warmhearted womanhood. As poet, philosopher and theologian, and through his (relative to any contemporary perspective) unusually high estimation of “the hjertelige [heart-led] gender” Grundtvig has devised a great corpus of symbolisations in which the feminine virtues are most highly valued, even to the extent of a complementary and equal valuation of the sexes. From it, succeeding generations - and women not least - have been able to draw human and political advantages and inspiration which is still far from exhausted. Indeed, appreciation of it is only now dawning on our own, perhaps sexually better balanced and spiritually better prepared age. Yet, notwithstanding many scattered sketches and a few more penetrating scholarly enquiries, this all-permeating sexual and critical aspect of Grundtvig’s thinking has never been the subject of a sufficiently comprehensive treatment.